TerapiadeantibióticosenhospitalizadosporCOVID-19:Revisiónsistemáticaconmeta-análisis - Coaguila Cusicanqui, Luis A. (2022)
Introducción:Elobjetivodelestudioestábasadoendeterminarsielusodeantibióticoterapiaempíricaaumentaelriesgodemuerteenlospacientesadultosmayoresde18añoshospitalizadosconCOVID-19.Métodos:Serealizóunarevisiónsistemáticaymeta-análisis,paralocualsetomóencuentaestudiosretrospectivosyprospectivos.ParalabúsquedasistemáticaseusaronlasbasesdedatoselectrónicasMedline/PubMed,Embase,LILACSyCINAHLenelperiododediciembre2019amayodel2021.SecalcularonlosOddsRatioylosintervalosdeconfianzaal95%utilizandoelefectoaleatorio,enfuncióndequeexistaonoheterogeneidad,seelaboróelgráficodeFunnelPlotparaevaluarelriesgodesesgo.Resultados:Selocalizaron528artículos,quecumplieronconloscriteriosdeinclusiónyexclusión,seevaluólaelegibilidaddelostextoscompletosde90estudios,deloscualessetuvocomoresultado10artículos.ElOddsRatiodelos10estudiosesde1,55(1,20-2,01),afavordelnousodeantibióticos,conunI2deheterogeneidadentrelosestudiosdel50%,ylaantibióticoterapiaempíricaguiadaconprocalcitonina<0,5ng/dlelOddsRatiofuede28,99(10,17-82,64)conunI2deheterogeneidaddel0%.Conclusión:LosresultadosnosindicanquealadministrarelantibióticosinevidenciadedatosmicrobiológicosaumentalamortalidadendichospacientesyalcontrarioelnousarantibióticoterapiaempíricareducelamortalidadenlospacientesinfectadosconCOVID-19gravesquellegaronaloshospitales.